2003
DOI: 10.1007/s00125-003-1213-6
|View full text |Cite
|
Sign up to set email alerts
|

The FOXC2 -512C>T variant is associated with hypertriglyceridaemia and increased serum C-peptide in Danish Caucasian glucose-tolerant subjects

Abstract: Aims/hypothesis. The transcription factor FOXC2 plays a key role in adipocyte differentiation and the FOXC2 gene is a candidate gene for Type 2 diabetes, obesity and dyslipidaemia. We investigated whether the FOXC2 -512C>T promoter variant is associated with Type 2 diabetes or its intermediary phenotypes in glucose tolerant subjects. Methods. The variant was genotyped using PCR-RFLP in 705 unrelated Type 2 diabetic patients, 505 unrelated glucose-tolerant control subjects and 219 glucose-tolerant offspring of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
(14 reference statements)
1
11
2
Order By: Relevance
“…7,8 Although these data identified FOXC2 as a candidate gene for insulin resistance and/or type 2 diabetes, three recent reports in Japanese, Pima Indians and Danish Caucasians have failed to identify an association between FOXC2 and type 2 diabetes. [8][9][10] In addition, contrasting with previous data, the Tallele was weakly associated with increased waist-to-hip ratio (WHR), plasma triglycerides and measures of insulin resistance in the Danish study. 10 Insulin resistance and additional features of the metabolic, or rather dysmetabolic, syndrome including abdominal obesity, hypertension and dyslipidemia are under strong genetic influence and cluster in families and they are the hallmark feature of type 2 diabetes.…”
Section: Introductioncontrasting
confidence: 90%
See 2 more Smart Citations
“…7,8 Although these data identified FOXC2 as a candidate gene for insulin resistance and/or type 2 diabetes, three recent reports in Japanese, Pima Indians and Danish Caucasians have failed to identify an association between FOXC2 and type 2 diabetes. [8][9][10] In addition, contrasting with previous data, the Tallele was weakly associated with increased waist-to-hip ratio (WHR), plasma triglycerides and measures of insulin resistance in the Danish study. 10 Insulin resistance and additional features of the metabolic, or rather dysmetabolic, syndrome including abdominal obesity, hypertension and dyslipidemia are under strong genetic influence and cluster in families and they are the hallmark feature of type 2 diabetes.…”
Section: Introductioncontrasting
confidence: 90%
“…[8][9][10] In addition, contrasting with previous data, the Tallele was weakly associated with increased waist-to-hip ratio (WHR), plasma triglycerides and measures of insulin resistance in the Danish study. 10 Insulin resistance and additional features of the metabolic, or rather dysmetabolic, syndrome including abdominal obesity, hypertension and dyslipidemia are under strong genetic influence and cluster in families and they are the hallmark feature of type 2 diabetes. 11 A concomitant diagnosis of dysmetabolic syndrome is present in up to 80% of type 2 diabetic patients and is associated with a doubling of the risk for cardiovascular morbidity and mortality.…”
Section: Introductioncontrasting
confidence: 90%
See 1 more Smart Citation
“…
Letters 757Lack of association between metabolic traits and the −512 polymorphism in FOXC2 in German people with normal glucose toleranceTo the Editor: A recent paper reported an association between the −512C>T promoter polymorphism in the forkhead box C2 (FOXC2) gene and increased serum C-peptide and hypertriglyceridaemia in normal-glucose-tolerant subjects from Denmark [1]. An association with Type 2 diabetes was not observed in this population.
…”
mentioning
confidence: 97%
“…For example, in comparison with the Danish report [1], we studied younger subjects with a higher proportion of positive family history of Type 2 diabetes. The Danish study reported marginally higher fasting insulin and significantly higher fasting C-peptide in carriers of the T-allele.…”
mentioning
confidence: 99%